2023
DOI: 10.26668/businessreview/2023.v8i2.1384
|View full text |Cite
|
Sign up to set email alerts
|

Disposition Effect: Does Investor Confidence Matter? Examining Service From Securities Brokerages

Abstract: Purpose: This study aims to analyze the role of training program to develop novice investors confidence in buying a stock. Novice investors undergo dilemma to buy stock due to limited knowledge which resulting disposition effect. Research regarding disposition effect which associated with training for novice investors is still limited   Theoretical framework: The disposition effect is the tendency when investors sell stocks that have the potential to experience future profits early, otherwise inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Alternatively, investment can be defined as that part of the national product that was not used for the current consumption during a specific year, but used to aggregate capital assets of a community to increase the capability of that country to produce goods. Great economist Keynes defined investment as being "the value of current production of capital goods and value of finished goods aggregated to the inventory; or else it is the net increase in real capital, equipment and goods (David W, 1981, Yulianto & Wijaya 2023. However, the UN Conference on Trade and Development UNCTAD defined foreign investment as "a long-term relationship reflecting the permanent interest and control of entity residing in an economy (i.e.…”
Section: Second: Economical Concept Of Investmentmentioning
confidence: 99%
“…Alternatively, investment can be defined as that part of the national product that was not used for the current consumption during a specific year, but used to aggregate capital assets of a community to increase the capability of that country to produce goods. Great economist Keynes defined investment as being "the value of current production of capital goods and value of finished goods aggregated to the inventory; or else it is the net increase in real capital, equipment and goods (David W, 1981, Yulianto & Wijaya 2023. However, the UN Conference on Trade and Development UNCTAD defined foreign investment as "a long-term relationship reflecting the permanent interest and control of entity residing in an economy (i.e.…”
Section: Second: Economical Concept Of Investmentmentioning
confidence: 99%
“…That reduces risks in lending activities, thereby making the bank more stable (Ho & Michaely, 1988;Williamson, 2000). Yulianto & Wijaya (2023) showed that the training program and investor experience impact investor confidence. More importantly, the behavior of bank managers can vary in different contexts regarding the economic situation and conditions of their banks (Vo & Nguyen, 2014).…”
Section: Introductionmentioning
confidence: 99%